Contingent convergence: a comparative analysis of activation policies - Werner Eichhorst; Regina Konle-Seidl (Institute for the Study of Labor (IZA), 2008)
The trend towards activation has been one of the major issues in recent welfare and labour market reforms in Europe and the US. Despite considerable initial variation across national models with respect to the scope and intensity of activation, redefining the link between social protection and labour market policies on the one hand and employment on the other has been a common issue in labour market reforms. The paper shows the development of activation policies in terms of basic principles, instruments, target groups and governance in Germany, France, the Netherlands, Switzerland, the United Kingdom, the US, Sweden and Denmark. It assesses the effectiveness and efficiency of activation policies in terms of bringing the jobless into work and ensuring sustainable independence from social benefits. Based on national activation trajectories, the paper argues that we can observe a contingent convergence of instruments, target groups, governance modes and outcomes so that established typologies of activation strategies have to be questioned.
urn:nbn:de:101:1-20090107110
Keywords: J65; J68; 330; Activation; active labor market policies; unemployment insurance; social assistance; Arbeitslosenversicherung; Reform; Aktivierende Sozialhilfe; Sozialreform; Arbeitsmarktpolitik; Policy-Mix; Vergleich; Deutschland; Frankreich; Niederlande; USA; Schweden; Dänemark; Schweiz; Großbritannien